Knowledge and menstrual hygiene practices among adolescent secondary school girls in Ebonyi State, Nigeria - Obande-Ogbuinya, Nkiru E.; Chikezie, Oluchi C.; John-Paul Bassey, Owojokane; Chinemerem, Ashang H.; Edward, Offionor C.; Uzoho, Chibuzo M.; Omaka-Amari, Lois N.; Nwafor, Jude N.; Aleke, Christian O.; Nweke, Ogbonna J.; EjibeOfor, Daniel C. (International Journal Of Community Medicine And Public Health, 2022)
Background: Menstrual hygiene is an aspect of sexuality education that people do not want to discuss publicly. Because of this most adolescent girl are bereaved of knowledge about menstrual hygiene practices. Therefore, the present study attempted to ascertain the knowledge and menstrual hygiene practices among adolescent secondary school girls in Ebonyi state, Nigeria. Methods: This was an institutional based cross-sectional study conducted from 11th July to 9th September 2021 among adolescent secondary school girls in Ikwo local government area, Ebonyi State, Nigeria. Data were collected from 400 participant using administered questionnaire. However, out of 400 participants, 315 properly filled and fit for analysis. Result: From a total of 315 adolescent girls participated in this study, majority 251 (79.7%) of the girls possess good knowledge while 64 (20.3%) has poor knowledge of menstrual hygiene practices. The result further indicated a significant association between the age groups (Chi square=10.862; p=0.004 <0.05); class level (Chi square=23.601; p=0.000<0.05) and the knowledge of menstrual hygiene practices among the adolescents’ girls respectively. Conclusions: There is need for government at all level, health educators and parents to design acceptable awareness creation and advocacy programs to improve the knowledge especially among adolescent girls at their early adolescents and those at lower class and so as to promote safe hygienic practices during menstruation.